Situation Report: Czechoslovakia, 20 October 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Czech Poet Jaroslav Seifert Awarded the Nobel Prize for Literature Steep Price Hikes for Beer and Other Beverages Strougal Turns 60 The Third Wave of Refugees What Is Wrong with Investments in Machinery and Equipment